Manajemen Kesan Remaja di Instagram: Negosiasi Identitas dalam Standar Penampilan Digital - Maysha Octavia; Rizki Setiawan (Universitas Hamzanwadi, 2026)
The increasing use of Instagram as a space for self-expression encourages adolescents to align their self-image with digital appearance standards that emphasize visual aesthetics and social acceptance. This study aims to describe adolescents’ impression management strategies in coping with appearance standards on Instagram, identify factors influencing the formation of digital self-image, and analyze the implications for digital identity and psychological well-being. The study employed a descriptive qualitative approach involving five female adolescent informants aged 18–21 who actively use Instagram and reside in Serang City and outside the region. Data were collected through in-depth interviews and observation of Instagram accounts, then analyzed using the Miles and Huberman interactive model. The results indicate that adolescents manage their image through post selection, filter use, audience control, and the separation of public and private spaces. These practices are influenced by internal and external factors and demonstrate that self-image formation occurs through a process of negotiation between individual preferences, social expectations, and the characteristics of digital platforms. This study concludes that Instagram serves as a space for the negotiation of adolescent identity and contributes to the understanding that impression management practices are not entirely controlled by individuals but are also shaped by social contexts and platform mechanisms.